نطاق سلطة القاضي في العقد على ضوء أحكام القانون المدني الجزائري - صوراية منصوري; نوال خليل (My University, 2024)
Abstract : The judge’s authority to create contractual balance is one of the most important mechanisms adopted by the legislator to achieve contractual justice, protect the weak party from, and maintain contract stability and contractual security on the other hand. However, this authority is considered a departure from the legal principle represented in “the contract is the law of the contracting parties.” If the will of the parties is The basis for concluding contracts and giving them the desired legal description. Circumstances and circumstances may arise, whether at the stage of concluding the contract, such as if the contract includes a defect, fraud or exploitation, or includes arbitrary conditions that burden the compliant party, or at the stage of its implementation, in the event of an emergency circumstance occurring that makes the implementation of the obligation difficult. Onerous for the debtor, or in the case of a penal clause, and this is what made the judge’s amendment to the contract an inevitable necessity to restore balance between its parties. He intervenes with the aim of mitigating the negative effects resulting from the will of the parties on the one hand and with the aim of achieving contractual balance and achieving contractual justice on the other hand. ............................ الملخص : تعد سلطة القاضي في إحداث التوازن العقدي من اهم الآليات التي انتهجها المشرع لتحقيق العدالة العقدية وحماية الطرف الضعيف من والحفاظ على إستقرار العقود والامن التعاقدي من جهة أخرى إلا أن هذه السلطة تعتبر خروجا على مبدأ قانوني متمثل في "العقد شريعة المتعاقدين" فإذا كانت إرادة الأطراف هي الأساس في إبرام العقود و إعطائها الوصف القانوني المنشود فإنه قد تطرأ ظروف و أحوال سواء في مرحلة إبرام العقد كأن یتضمن العقد عيبا الغبن أو الإستغلال، أو أن یتضمن شروطا تعسفية ترهق الطرف المذعن، أوفي مرحلة تنفیذه و ذلك في حال حدوث ظرف طارئ يجعل تنفیذ الإلتزام مرهقا للمدین، أو في حال الشرط الجزائي و ، و هذا ما جعل تعدیل القاضي للعقد ضرورة حتمية لإعادة التوازن بین أطرافه، فیتدخل قصد التخفيف من الآثار السلبية الناتجة عن إرادة الأطراف من ناحية و بهدف تحقیق التوازن العقدي و تحقیق العدالة العقدية من ناحية أخرى. ........................ Réisme : Le pouvoir du juge de créer un équilibre contractuel est l'un des mécanismes les plus importants adoptés par le législateur pour parvenir à la justice contractuelle, protéger la partie faible et maintenir la stabilité et la sécurité contractuelles. Cependant, ce pouvoir est considéré comme une dérogation. le principe juridique représenté dans « le contrat est la loi des parties contractantes ». Si la volonté des parties est la base pour conclure des contrats et leur donner la description juridique souhaitée, des circonstances et des circonstances peuvent survenir, que ce soit au stade de la conclusion du contrat. contrat, par exemple si le contrat comporte un défaut, une fraude ou une exploitation, ou comprend des conditions arbitraires qui pèsent sur la partie conforme, ou au stade de son exécution, en cas de survenance d'une circonstance d'urgence qui rend difficile l'exécution de l'obligation. Onéreux pour le débiteur, ou dans le cas d'une clause pénale, et c'est ce qui a fait de la modification du contrat par le juge une nécessité inévitable pour rétablir l'équilibre entre ses parties. Il intervient dans le but d'atténuer les effets négatifs résultant de la volonté du débiteur. entre les parties d'une part et dans le but de parvenir à l'équilibre contractuel et à la justice contractuelle d'autre part.
Keywords: Keywords: judge’s authority; contract amendment; contractual balance; contractual justice.; الكلمات المفتاحية: سلطة القاضي، تعدیل العقد، التوازن العقدي، العدالة العقدية .; Mots-clés : autorité du juge; avenant au contrat; équilibre contractuel; justice contractuelle.